2011
DOI: 10.1093/annonc/mdq393
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin D multiple myeloma: response to therapy, survival, and prognostic factors in 75 patients

Abstract: IgD MM is an aggressive disease that is usually detected at an advanced stage. Despite a positive initial response, survival after relapse was dismal. Intensive treatment strategies before and following stem cell transplantation may improve outcomes in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 19 publications
7
34
1
5
Order By: Relevance
“…67% of patients had stage 3 or higher stage disease. [7][8][9] Our case is different from other cases in the literature with having no symptoms except fatigue and widespread body pain and being older than other cases.…”
Section: Discussioncontrasting
confidence: 83%
“…67% of patients had stage 3 or higher stage disease. [7][8][9] Our case is different from other cases in the literature with having no symptoms except fatigue and widespread body pain and being older than other cases.…”
Section: Discussioncontrasting
confidence: 83%
“…Five studies, each including at least 20 patients with IgD-associated multiple myeloma, have been published to date. [1][2][3][4][5] This entity appears to have clinical differences compared with non-IgD myeloma, including a younger age at disease presentation and a higher incidence of extramedullary disease. Some have suggested that patients with IgD myeloma have a greater degree of renal insufficiency at presentation.…”
Section: Introductionmentioning
confidence: 99%
“…This is a rare entity with very low incidence that accounts for less than 2% of total MM cases and it is characterized to have poor prognosis; the median survival time is 12 months following diagnosis [3] or at most, two years [4]. In the clinical characteristic of IgD MM patients, Kim et al found a younger age at time of presentation with advanced stage and a more aggressive clinical course [5]. In a cases series of 53 patients with IgD MM described by Blade et al, they reported the main presenting features were bone pain (72%), fatigue (36%), renal function impairment (33%), weight loss (32%), hypercalcemia (22%), extramedullary plasmacytomas (19%) and associated amyloidosis (19%) [6].…”
Section: Discussionmentioning
confidence: 99%